1997
DOI: 10.1177/00220345970760071001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mercury Vapor and Impact on Health in the Dental Profession in Sweden

Abstract: Possible adverse effects of mercury exposure in dentistry have been discussed in several studies. The objective of the present study was to carry out detailed measurements of mercury exposure in the dental profession in Sweden, and to search for adverse health effects from such exposure. We examined 22 dentists and 22 dental nurses, working in teams, at six Swedish dental clinics. Measurements of air mercury, performed with personal, active air samplers, showed a median air Hg of 1.8 micrograms/m3 for the dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
2
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 25 publications
6
61
2
7
Order By: Relevance
“…In Sweden, the exposure to Hg vapor in the dental profession was much lower in 1986 and in 1997 comparable to the American data. The mean values for Hg-U in the dental [10,13]. In some countries, the mean and range of Hg-U concentrations in the dental staff are still rather high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, the exposure to Hg vapor in the dental profession was much lower in 1986 and in 1997 comparable to the American data. The mean values for Hg-U in the dental [10,13]. In some countries, the mean and range of Hg-U concentrations in the dental staff are still rather high.…”
Section: Discussionmentioning
confidence: 99%
“…To assess low-level occupational mercury exposure of dental staff, urine mercury (Hg-U) concentration was used as an exposure index [4,[6][7][8][9][10][11][12][13][14][15][16]. The recent literature data confi rm that Hg-U remains the most practical and sensitive marker of monitoring low-level occupational exposure to inorganic mercury [7].…”
Section: Ijomeh 2007;20(2) 148mentioning
confidence: 99%
“…The way in which amalgam is prepared, cleaning habits, and types of floor coverings have been pointed out to be important factors. 24 In this study the blood results were obtained by considering the plasma and erythrocyte ratio (2/3). 19 The study demonstrated that the increase of total mercury in plasma and blood was significant in groups IV, V, and particularly in the teaching staff (Group VI) who worked with amalgam.…”
Section: Discussionmentioning
confidence: 99%
“…Human toxicological data about methylmercury poisoning show that symptoms of toxic effects appear at a concentration of mercury in blood of 0.1 µg/mL and death occurs at concentrations above 3 µg/mL (9). It has also been reported that professional exposure to mercury vapor and the release of mercury from or during the removal of amalgam dental fillings increases the blood and plasma concentration of the metal (18)(19)(20). After exposure to mercury vapor, blood concentrations attain 18 nM (20) and, after exposure to dental amalgam fillings and their removal, plasma concentration attains 5 nM (19).…”
Section: Mercurymentioning
confidence: 99%
“…It has also been reported that professional exposure to mercury vapor and the release of mercury from or during the removal of amalgam dental fillings increases the blood and plasma concentration of the metal (18)(19)(20). After exposure to mercury vapor, blood concentrations attain 18 nM (20) and, after exposure to dental amalgam fillings and their removal, plasma concentration attains 5 nM (19). Another important mechanism of exposure is fish consumption.…”
Section: Mercurymentioning
confidence: 99%